DEVELOPMENT OF INTERACTIVE E-BOOKS ON DIGITAL CIRCUITS TO IMPROVE TECHNOLOGY AND ENGINEERING LITERACY SKILLS FOR ELECTRICAL ENGINEERING EDUCATION STUDENTS - Nurulita Imansari; Pramudya Ardi; Prabakti Endramawan (Jurnal Education and Development, 2022)
The purpose of this research is to develop an interactive e-book for digital circuit courses. The development is carried out using 4D which consists of define, design, development and disseminate. To test the validity of the e-book, validation was carried out by media experts and material experts, while the effectiveness test related to technology and engineering literacy skills was carried out using a questionnaire on 20 students. The results of expert validation show that interactive e-books are in the excellent category so that they are feasible to use. The results of the effectiveness test show that interactive e-books are effective for improving technology and engineering literacy for electrical engineering students.